UPAYA PENINGKATAN DISIPLIN KEHADIRAN GURU MELALUI KETELADANAN KEPALA SEKOLAH DI MTsN 3 BUTON TENGAH - SAMIUDDIN SAMIUDDIN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This research is School Action Research which aims to determine the improvement of teacher discipline in teaching attendance in the classroom through the example of the Principal at MTs Negeri 3 Buton Tengah for the 2021/2022 academic year. The subjects of this study were 15 teachers of MTs Negeri 3 Buton Tengah. This research was conducted in the even semester of the 2021/2022 academic year. The results showed that the exemplary principal can improve teacher discipline in teaching attendance in class, where in the implementation of pre-cycle learning at the first meeting all teachers were present on time, because it was the first day of school for the 2012/2022 school year. The implementation of learning in the first cycle there were 12 teachers who were late to teach in class, and after the implementation of learning in the second cycle the teacher's discipline in teaching attendance in class reached 80% based on the responses of respondents (teachers) regarding the example of the Principal, while based on the results of observations 77% Teachers who are still less than 5 minutes late, because the location of the school is far and difficult to reach. ABSTRAKPenelitian ini adalah Penelitian Tindakan Sekolah (School Action Research) yang bertujuan untuk mengetahui peningkatan disiplin guru dalam kehadiran mengajar di kelas melalui keteladanan Kepala Sekolah di MTs Negeri 3 Buton Tengah tahun pelajaran 2021/2022. Subjek penelitian ini adalah guru MTs Negeri 3 Buton Tengah sebanyak 15 orang. Penelitian ini dilaksanakan pada semester genap tahun pelajaran 2021/2022. Hasil penelitian menunjukkan bahwa Keteladanan Kepala Sekolah dapat meningkatkan Kedisiplinan guru dalam kehadiran mengajar di kelas, dimana pada pelaksanaan pembelajaran pra-siklus pada pertemuan pertama semua Guru hadir tepat waktu, karena merupakan hari pertama sekolah untuk tahun pelajaran 2012/2022. Pelaksanaan pembelajaran pada siklus I ada 12 orang Guru yang terlambat masuk mengajar di kelas, dan setelah pelaksanaan pembelajaran pada siklus II kedisiplinan guru dalam kehadiran mengajar di kelas mencapai 80% berdasarkan tanggapan responden (guru) mengenai keteladanan Kepala Sekolah, sedangkan berdasarkan hasil observasi 77 % Guru yang masih terlambat kurang dari 5 menit, karena lokasi sekolah yang jauh dan sulit terjangkau.